2016
DOI: 10.1371/journal.pone.0151206
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Genetic Composition of a Medieval Population from a Hungarian-Slavic Contact Zone in Central Europe

Abstract: The genetic composition of the medieval populations of Central Europe has been poorly investigated to date. In particular, the region of modern-day Slovakia is a blank spot in archaeogenetic research. This paper reports the study of mitochondrial DNA (mtDNA) in ancient samples from the 9th–12th centuries originating from the cemeteries discovered in Nitra-Šindolka and Čakajovce, located in western Slovakia (Central Europe). This geographical region is interesting to study because its medieval multi-ethnic popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
1
27
0
3
Order By: Relevance
“…The legend shows the color code of compared historical Eurasian populations. Abbreviations and references for individual populations: HUN_C, population from Hungarian conquest‐period (Hungary) (Csösz et al, 2016; Tömöry et al, ); HUN_AV, medieval Avar population (Hungary) (Csösz et al, 2016) ; CB_CZ, two medieval Hungarian‐Slavic contact zone populations (Slovakia, Croatia) (Csákyová et al, ; Csösz et al, 2016); HUN_L, medieval Lombard population from Szölád (Hungary) (Alt et al, ); ITA_L, medieval Lombards from Piedmont region (Italy) (Vai et al, ); ITA_m, medieval population from Tuscany (Italy) (Guimaraes et al, ); SPA_m, medieval Spaniard population (Spain) (Alzualde et al, ); POL_m, medieval Slavic population (Poland) (Juras et al, 2015); ICE_m, medieval Icelandic population (Iceland) (Helgason et al, ); DAN_V, medieval population of Danes and Vikings (Denmark); NOR_V, medieval population of Norwegian Vikings (Norway) (Krzewińska et al, ); MON_X, nomadic Xiongnu population (Mongolia) (Keyser‐Tracqui et al, (); Kim et al, ); CHIN_X, Xianbei population (inner Mongolia, China) (Changchun et al, ); CHIN_WZ, populations from Wanggu and Zhenzishan (inner Mongolia, China) (Fu et al, ); RUS_Y, Yakut population from eastern Siberia (Sakha republic, Russia) (Crubézy et al, ); MIN_BR, Bronze Age populations from south Siberia/central Asia (Russia) (Allentoft et al, ; Keyser et al ); KAZ_BRIA, Bronze and Iron Age populations from central Asia (Kazakhstan) (Allentoft et al, ; Lalueza‐Fox et al, ); ALT_Sc, Iron Age Scytho‐Siberian population (Altai Republic, Russia/Mongolia) (Allentoft et al, ; González‐Ruiz et al, ; Pilipenko et al, Ricaut et al, ); SIB_K, Bronze Age population of Late Krotovo culture from western Siberia (Russia) (Molodin et al, ); SIB_B, Bronze Age population from western Siberia (Baraba steppe) (Rusiia) (Molodin et al, ); SIB_A Bronze Age population of Andronovo culture from western Siberia (Russia) (Allentoft et al, ; Molodin et al, )…”
Section: Discussionmentioning
confidence: 99%
“…The legend shows the color code of compared historical Eurasian populations. Abbreviations and references for individual populations: HUN_C, population from Hungarian conquest‐period (Hungary) (Csösz et al, 2016; Tömöry et al, ); HUN_AV, medieval Avar population (Hungary) (Csösz et al, 2016) ; CB_CZ, two medieval Hungarian‐Slavic contact zone populations (Slovakia, Croatia) (Csákyová et al, ; Csösz et al, 2016); HUN_L, medieval Lombard population from Szölád (Hungary) (Alt et al, ); ITA_L, medieval Lombards from Piedmont region (Italy) (Vai et al, ); ITA_m, medieval population from Tuscany (Italy) (Guimaraes et al, ); SPA_m, medieval Spaniard population (Spain) (Alzualde et al, ); POL_m, medieval Slavic population (Poland) (Juras et al, 2015); ICE_m, medieval Icelandic population (Iceland) (Helgason et al, ); DAN_V, medieval population of Danes and Vikings (Denmark); NOR_V, medieval population of Norwegian Vikings (Norway) (Krzewińska et al, ); MON_X, nomadic Xiongnu population (Mongolia) (Keyser‐Tracqui et al, (); Kim et al, ); CHIN_X, Xianbei population (inner Mongolia, China) (Changchun et al, ); CHIN_WZ, populations from Wanggu and Zhenzishan (inner Mongolia, China) (Fu et al, ); RUS_Y, Yakut population from eastern Siberia (Sakha republic, Russia) (Crubézy et al, ); MIN_BR, Bronze Age populations from south Siberia/central Asia (Russia) (Allentoft et al, ; Keyser et al ); KAZ_BRIA, Bronze and Iron Age populations from central Asia (Kazakhstan) (Allentoft et al, ; Lalueza‐Fox et al, ); ALT_Sc, Iron Age Scytho‐Siberian population (Altai Republic, Russia/Mongolia) (Allentoft et al, ; González‐Ruiz et al, ; Pilipenko et al, Ricaut et al, ); SIB_K, Bronze Age population of Late Krotovo culture from western Siberia (Russia) (Molodin et al, ); SIB_B, Bronze Age population from western Siberia (Baraba steppe) (Rusiia) (Molodin et al, ); SIB_A Bronze Age population of Andronovo culture from western Siberia (Russia) (Allentoft et al, ; Molodin et al, )…”
Section: Discussionmentioning
confidence: 99%
“…Networks were subjected to maximum parsimony post-analysis. Haplogroup frequencies for medieval populations were retrieved from previously published data as outlined in 18 . Since the vast majority of studies provided haplogroup frequencies inferred from HVRI, we reassigned the newly reported LC and NLC to haplogroups employing only this region.…”
Section: Mitochondrial Haplogroup Definition and Population Genetics mentioning
confidence: 99%
“…Of the typed 111 mtDNA profiles, we excluded the site Vörs-Papkert from the population genetic analyses, because it represents a 9 th -10 th -century late Avar-Slavic mixed population in Transdanubia (western-Hungary). On the other hand, we included 26 samples from medieval Hungary described by Tömöry et al 12 , and 19 samples from medieval Č akajovce (today's Slovakia) described by Csákyova et al 13 ( Supplementary Table S4).…”
Section: Reference Population Datamentioning
confidence: 99%
“…The analysis was performed in Arlequin software, using Tamura & Nei substitution model 47 Sizes of circles indicate number of obtained mtDNA haplotypes from a certain site. Italic letters (17-30) mark previously published data 12,13 . Green color indicates Avar cemeteries, red color designates conqueror cemeteries, blue shows the contact zone, and black indicates 9 th -10 th century late Avar populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation